Exploring the Emotional Lives of Adolescent Athletes Under Competitive Pressure - Lee, Sophia; Matthews, Brian (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to explore the emotional experiences of adolescent athletes participating in competitive sports. Methods and Materials: This qualitative research employed a thematic analysis approach to investigate the emotional lives of adolescent athletes. Data were collected through semi-structured interviews with 26 participants aged 14–18 years, all of whom were active in competitive sports across various disciplines in the United States. Participants were selected using purposive sampling, and interviews continued until theoretical saturation was achieved. Interviews were transcribed verbatim and analyzed using NVivo software to identify key themes and patterns within the data. Findings: Three major themes emerged from the analysis: emotional responses to competitive pressure, coping strategies and emotional regulation, and external influences on emotional experiences. Participants reported intense emotional fluctuations, including performance anxiety, emotional highs and lows, emotional suppression, and burnout symptoms. Coping strategies included cognitive reframing, social support, and pre-competition rituals. External influences such as coaching style, parental expectations, peer comparison, and social media presence significantly shaped emotional responses. The findings highlight both the vulnerability and adaptive capabilities of adolescent athletes in emotionally demanding sport environments. Conclusion: Adolescent athletes face a complex emotional landscape in competitive sports, influenced by internal expectations and external pressures. While many develop effective coping mechanisms, others struggle with emotional suppression and burnout. Supporting emotional awareness and regulation within youth sports is essential for promoting long-term psychological well-being and sustained participation.